KINETOSTATIC CALCULATION OF A HIGH CLASS LIFTING MECHANISM (BY ASSUR CLASSIFICATION) OF A TECHNOLOGICAL LOAD-LIFTING MACHINE (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2023)
To improve the technical level of mechanical engineering, it is necessary to expand the technical capabilities of equipment and devices, existing structures, as well as equipping them with fundamentally new mechanisms. The creation of new designs of machines and mechanisms requires the design of lever mechanisms of high classes, the working bodies of which can reproduce complex movements and trajectories. Due to the presence of movable, variable closed hinge-lever contours, lever mechanisms of high classes, unlike traditional lever mechanisms with lower pairs, perceive heavy loads, have increased rigidity.On the basis of a high-class rectilinear guiding mechanism, a lever mechanism has been designed that can be used in lifting machines and mechanisms. An important machine kinetics section is the force analysis of mechanisms by the given laws of motion of the initial elements and known external forces applied to the mechanism segments. The paper proposes a new design of a lifting mechanism, the peculiarity of which is that it belongs to the high-class Assur group by its structure, which causes ease of operation and reliability of the design. For this design, a synthesis of the mechanism was carried out in [1], and now a force analysis of this mechanism is being performed using the Academician U.A. Dzholdasbekov method of introducing auxiliary points.